(Trans)formações na identidade docente durante a formação inicial no PIBID inglês - Pereira, Josilene Carvalho (2021)
This research aims at investigating how student teachers’ sayings are constructed in their experience reports and what meanings they (re)constructed during their participation in the Institutional Scholarship Program for Initiation to Teaching - PIBID, subproject - English Letters of a Federal University of the State of Minas Gerais - Brazil. Seeking to identify how the activities developed in the program helped in the construction of the teaching identity of these participants, a qualitative research (Minayo, 2004; Flick, 2009) was carried out, with the purpose of analyzing and discussing the students’ final reflectionsinf portfolios and especifically, their professional identity construction. The interpretation of the data, in addition to being based on concepts of English teacher development and teaching identity, also relies on principles of the Systemic-Functional Grammar (Halliday, 2004). The results of this research reflect how the PIBID program contributed to learning by giving a new meaning to the teaching identity of the participants, as they indicate that PIBID contributes directly to their development, preparing them for the beginning of their careers, in addition to allowing opportunities experience the pedagogical practice, as well as reflecting on their professional learnings. As such, this research may also be considered as input for discussions in the area of teacher education.